ON THE INFLUENCE OF THE ELASTIC ANISOTROPY OF THE PROPELLER ON THE VIBRATIONS OF AZIMUTH THRUSTERS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
A possibility for excitation of oscillations from the propeller of azimuth thrusters is analyzed.. The shaft is short, cantilever type. The propeller blades create elastic anisotropy of the propeller shaft with respect to the transverse stiffness. The influence of the elastic anisotropy of the propeller shaft on the oscillations of azimuth thrusters is studied . A mathematical model describing the oscillations is proposed, which is reduced to the Mathieu equation. It is proven that the elastic anisotropy of the propeller shaft excites two types of oscillations: forced with a blade frequency and multiples of it, and parametric with a frequency equal to half the blade frequency and multiples of it. Experimental results are presented.